In-Plane Shear Behavior of Stone Masonry Panels Strengthened through Grout Injection and Fiber Reinforced Cementitious Matrices. Issue 10 (3rd October 2021) - Ferretti, Francesca; Incerti, Andrea; Tilocca, Anna Rosa; Mazzotti, Claudio
ABSTRACT: Existing stone masonry buildings, constituting a significant portion of historical city centers, suffered often severe damages during seismic events. Traditional and innovative strengthening techniques can be applied to restore or enhance the structural capacity of these construction typologies. The objective of the present work was to evaluate the improvement given by different strengthening procedures to the shear behavior of stone masonry elements. In particular, an experimental campaign on stone masonry samples was carried out, in which the specimens were strengthened through different Fiber Reinforced Cementitious Matrix (FRCM) systems and grout injection. Non-destructive sonic tests were performed before and after the strengthening procedure to determine the efficiency of the grout injection. Then, the samples were subject to diagonal compression test with the objective of evaluating the influence of the different FRCM strengthening systems on the shear behavior, in terms of stiffness, load bearing capacity and failure mode. Comparisons between experimental results showed, on the one hand, a good correlation between the quality of the grout injection, analyzed through sonic tests, and the shear capacity of the retrofitted samples. On the other hand, the presence of the reinforcing fibers influenced mainly the post-peak behavior and determined a more ductile failure mode.